Pseudoporphyria Associated with Nonhemodialyzed Renal Insufficiency, Successfully Treated with Oral N-Acetylcysteine - A. C. Katoulis; D. Ferra; E. Toumbis; E. Papadavid; A. Kanelleas; I. Panayiotides; D. Rigopoulos (Hindawi Limited, 2013)
Pseudoporphyria (PP) is a relatively rare, photodistributed bullous dermatosis that resembles porphyria cutanea tarda (PCT), but it is not accompanied by porphyrin abnormalities in the serum, urine, or stool. It was initially described in renal failure patients on dialysis. Thereafter, it has been associated with several aetiological factors. We report a case of PP in a 67-year-old woman with mild renal failure, successfully treated with N-acetylcysteine. This is the second reported case of PP developing in nondialyzed chronic renal failure. Such cases support the view that renal impairment itself may play a more important aetiological role in developing PP than it was originally considered.